Bathymetry and Seabed Morphology Study for Determination of ASDP Shipping Line in Tanjungsau Island Waters, Batam - Melanie Rizky Hanuransyah; Alfi Satriadi; Kunarso Kunarso; Eka Bathin Putra; Jarot Marwoto (Indonesian Journal of Oceanography, 2020)
Tanjungsau Island Waters as the main gate of shipping line between Bintan Island and Batam need more attention for its shipping safety. The purpose of this research is to review the seabed morphology of Tanjungsau Island Waters, Batam for determination of ASDP shipping line. This research had been conducting from 3rd to 5th of Jule 2018 in The Tanjungsau Island Waters, Batam. The used data are depth measurement by singlebeam echosounder type Ceducer Pro, tidal data, ship draft, and Digital Map of Indonesia Sea edition 2013 Vol. 49 published by TNI-AL DISHIDROS. Data had processed by using ArcGIS 10.3 and Surfer 9 software to generate the bathymetry contour and the 3D model of seabed morphology. The result indicates that the depth ranged between -1,69 m to -17,58 m. The bathymetry contour map shows seabed morphology is a continental shelf. Based on the slope calculation, Tanjungsau Island Waters not only include flat category between 1,08% - 1,58% but also having a slope area worth 2,59%. The right ASDP shipping line from Bintan Island to Batam has the minimum depth -5,32 m with the largest ship draft which can enter approximately 4,788 m.